Countries Response for People With Disabilities During the COVID-19 Pandemic - Lugo-Agudelo, LH; Spir Brunal, Maria A; Posada Borrero, Ana M; Cruz Sarmiento, Kelly M; Velasquez Correa, Juan C; Di Dio Castagna Iannini, Rosarita; Gonzalez Zuluaga, Manuela; Ospina, Victor A; Patiño Lugo, Daniel F; Mesa Franco, Luisa F; Gutenbrunner, Christoph (Frontiers in Rehabilitation Sciences, 2022)
Background and objectives: During the Coronavirus (COVID-19) pandemic, isolation and prevention measures to reduce COVID-19 contagions are essential for the care of all people; these measures should comply with the principles of inclusion and accessibility for people with disabilities (PWD), with all kinds of deficiencies and levels of dependency. Thereby, the aim of this article is to present the measures adopted for PWD or people with rehabilitation needs, for containment, mitigation, or suppression of SARS-CoV-2 virus in different countries of all continents and of all income levels. Methods: A narrative approach was used to this article. First, a broad search was carried out in the 193 member states of the United Nations (ON), and then 98 countries that issued any document, report, or information related to disability and COVID-19 were selected. Finally, 32 countries were included in this article because they presented official information. We consider official sources the information available in the government or in the health ministry page of the country. In this way, the countries that presented information that did not correspond to an official source, were excluded. The search was conducted on August 2020 and updated on March 2021. Results: First, the non-pharmacological general interventions for PWD that included informative measures and general recommendations during the stay at home, isolation and biosecurity measures, contagion prevention, detection of positive cases, mobilization measures, and measures implemented in institutions or residences of PWD. Second, we identified the economic and social benefits provided to PWD during the pandemic. Finally, we identified the measures taken by countries according to the type of impairment (visual, hearing, physical, mental and cardiopulmonary impairment) during the COVID-19 pandemic. Conclusions: In response to the COVID-19 pandemic, only 50% of countries from the five world regions created and implemented specific measures for PWD to containment, mitigation, or suppression of the SARS-CoV-2 virus. There is very little specific information available about measures to continue with the care of people with rehabilitation needs and the long-term follow-up of people with disabilities, and to prevention and response to violence, especially for women with disabilities.